Does Continuous Sciatic Nerve Block Improve Postoperative Analgesia and Early Rehabilitation After Total Knee Arthroplasty?: A Prospective, Randomized, Double-Blinded Study. Issue 5 (1st August 2011) - Cappelleri, Gianluca; Ghisi, Daniela; Fanelli, Andrea; Albertin, Andrea; Somalvico, Francesco; Aldegheri, Giorgio
Abstract : Introduction: The aim of this prospective, randomized, double-blind study was to evaluate whether continuous sciatic nerve block can improve postoperative pain relief and early rehabilitation compared with single-injection sciatic nerve block in patients undergoing total knee arthroplasty (TKA) and lumbar plexus block. Methods: After ethical committee approval and written informed consent, 38 patients with ASA physical status I to II were enrolled. The first group received continuous sciatic and continuous lumbar plexus blocks (group regional or R, n = 19), whereas the second group received a single sciatic nerve block followed by saline infusion through the sciatic catheter and continuous lumbar plexus block (group control or C, n = 19). We assessed morphine consumption, scores for visual analog scale for pain at rest (VASr), and during continuous passive motion (VASi during CPM) for 48 hours postoperatively. Effectiveness of early ambulation was also evaluated. Results: Scores for VASr and VASi during CPM, as well as morphine consumption, were significantly higher in group C than in group R ( P < 0.01). Moreover, patients in group R showed earlier rehabilitation with more effective ambulation ( P < 0.05). Conclusions: Continuous sciatic nerve block improves analgesia, decreases morphine request, and improves early rehabilitation compared with single-injection sciatic nerve block in patients undergoing TKA and lumbar plexus block.